The major role of riverine outflows in shaping the current and future habitats of Harmful Algal Blooms: the case of the North Sea - Olaf Duteil; Diego Macias; Adolf Stips; Luca Polimene (Environmental Research Communications)
This study investigates the extension of the potential habitat of Harmful Algal Blooms (HABs) in the North Sea using observational data and model experiments under current and future climate scenarios. We assess the combined effects of temperature, salinity, and nutrient availability, particularly the nitrogen-to-phosphorus ratio, on HABs in the region. Climate change projections indicate a decrease in salinity concomitant with an increase in surface temperature, potentially leading to an offshore extension of HAB habitat. Reducing nitrogen and phosphorus loads in rivers differentially affects dissolved inorganic nitrogen (DIN) and phosphorus (DIP) levels, with DIN being more sensitive to load reduction, thereby constraining HAB habitat extension. We underscore the importance of considering both physical and biogeochemical factors in assessing HAB habitat dynamics and the potential impacts of climate change and nutrient reduction measures on HAB expansion in the North Sea. These findings have significant implications for environmental policy and management.